Voting technology : the not-so-simple act of casting a ballot - Herrnson, Paul S., 1958- (Brookings Institution Press, 2008)
"Evaluates five commercially available voting systems, against different criteria (including ease of use, speed, and accuracy) using field and laboratory experiments and expert reviews. Initiates new research into interactions between ballot format and voter behavior. Offers best practices for voting system manufacturers, ballot designers, election officials, political observers, and voters"--Provided by publisher